2000
DOI: 10.1073/pnas.080076297
|View full text |Cite
|
Sign up to set email alerts
|

A highly digestible sorghum mutant cultivar exhibits a unique folded structure of endosperm protein bodies

Abstract: The endosperm of a sorghum mutant cultivar, with high in vitro uncooked and cooked protein digestibilities, was examined by transmission electron microscopy and ␣-, ␤-, and ␥-kafirins (storage proteins) were localized within its protein bodies. Transmission electron microscopy micrographs revealed that these protein bodies had a unique microstructure related to high protein digestibility. They were irregular in shape and had numerous invaginations, often reaching to the central area of the protein body. Protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
184
4
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(204 citation statements)
references
References 26 publications
8
184
4
6
Order By: Relevance
“…As explained, the improved protein digestibility of mutant sorghum lines, having highly invaginated protein bodies, is believed to be due to increased protein body surface area and easy accessibility of digestive enzymes to the more digestible alpha-kafirin proteins (Oria et al, 2000). In addition, the dense protein matrix observed in the TG lines, is probably composed of more digestible lysine-rich endogenous proteins, which would further improve the cooked IVPD of these lines.…”
Section: Endosperm Ultrastructurementioning
confidence: 99%
See 1 more Smart Citation
“…As explained, the improved protein digestibility of mutant sorghum lines, having highly invaginated protein bodies, is believed to be due to increased protein body surface area and easy accessibility of digestive enzymes to the more digestible alpha-kafirin proteins (Oria et al, 2000). In addition, the dense protein matrix observed in the TG lines, is probably composed of more digestible lysine-rich endogenous proteins, which would further improve the cooked IVPD of these lines.…”
Section: Endosperm Ultrastructurementioning
confidence: 99%
“…Breeding using P721 opaque line has been undertaken to produce high-lysine genotypes with improved grain hardness and protein digestibility after cooking (Tesso et al, 2006;Weaver et al, 1998). Electron microscopy and immunological studies of these high-lysine high-protein digestibility mutants showed their grain to have modified protein bodies (irregular shapes with deep invaginations), compared to the spherical protein bodies of normal sorghums (Oria et al, 2000). The location and organisation of different kafirin sub-classes within the protein bodies also differed with the gamma-kafirins being located at the bottom of folds, exposing the more digestible alpha-kafirins to digestive enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…However, in these HD mutants the protein bodies are very folded (invaginated) (Figure 1c), with the gammakafirin located at the base of the invaginations (14), with the effect that proteases have easy accessibility to the alpha-kafirin. Thus, it appears that reason for the high digestibility of the protein bodies the TG lines is different from that in the HD types.…”
Section: Pepsin Digestion Of the Pp By Starch Digestionmentioning
confidence: 99%
“…The higher protein digestibility of these lines was attributed to the fact that their protein bodies (the organelles of kafirin storage) are invaginated in shape, instead of being spherical (Oria et al, 2000). Recent research indicates that the invaginated shape of the .…”
Section: Proteinmentioning
confidence: 99%
“…They noted that in sorghum the protein bodies are difficult to disrupt and therefore in normal sorghum flour the protein is effectively inert as it is contained in the protein body (Goodall et al, 2012). However, in the case of the high protein digestibility mutant, the protein bodies have substantially lost their integrity (Oria et al, 2000) and the protein is much more available. Using this mutant it has been shown that doughs enriched with wheat gluten showed better rheological properties than similarly enriched doughs from normal sorghum and the resulting bread had higher loaf volume (Goodall et al, 2012).…”
Section: Protein Functionality For Quality Baked Goodsmentioning
confidence: 99%